The effect of a short-term training period on physiological parameters and running performance: intensity distribution versus constant-intensity exercise - Clemente-Suarez, V.; Dalamitros, A.; Nikolaides, P. T. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: This study compared the effect of two training strategies differing on the weekly intensity distribution on physiological parameters and running performance in moderately trained endurance athletes. METHODS: Thirty male athletes were equally divided into three groups, one following an increasing weekly aerobic intensity distribution (EXP1), one with constant weekly aerobic intensity distribution (EXP2) and a control one, following a freely chosen program (CON). Before the training intervention, athletes performed a maximal exercise treadmill test to quantify the different zones allowing training to be controlled, based on blood lactate concentration values (BLa), over a 4-week period. Changes in exercise heart rate (HR), running velocity and rate of perceived exertion at three exercise intensities corresponding to 2.5, 4 and 8 mmol·L-1 of BLa were analyzed at three testing conditions: before (pre), after two (mid) and four weeks (post). RESULTS: A significant increase (P=0.05) in running velocity at the intensity of 8 mmol·L-1 in EXP1 group was revealed at mid (5.5%) and postcondition (11.5%), while EXP2 group showed a significant decrease in exercise HR at 4 mmol·L-1 between pre- (6.7%) and post-condition (9.0%) (P=0.05). The rest of the examined variables showed only trivial changes in both experimental groups at all testing conditions (P>0.05). In addition, no changes were observed in CON group in any of the variables tested. CONCLUSIONS: These results demonstrate that depending on the training goal, different intensity variation strategies should be followed to induce the desired adaptations.